Testing for the existence of a bubble in the stock market - Dieter Gerdesmeier; Hans-Eggert Reimers; Barbara Roffia (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2013)
Are specific developments in stock prices in line with fundamentals or do they reflect a rising bubble? And if the latter result applies, how is it possible to detect a bubble in real time? The answer to this question is of utmost relevance for a number of areas, not least for either financial market participants or for central banks aiming at pursuing a policy of 'leaning against the wind'. In this study, we make use of a sample of 17 OECD industrialised countries and the euro area over the sample period 1969 Q1 - 2008 Q3 and carry out univariate and multivariate panel tests to find evidence of bubbles in the stock market of those countries over the past four decades.
Keywords: E37; E44; E51; 330